Development of Letshoot Applications as an Instructional Media of Computer Network Troubleshooting - Atista, Fadila Aini; Hatta, Puspanda; Wihidayat, Endar S (Universitas Sebelas Maret, 2017)
Based on the observations made in Class XII TKJ SMK Negeri 1 Banyudono, it is known that the interest of students on computer network troubleshooting material is low because the learning materials are delivered through the presentation media in one direction from teacher to student. This makes students less understand the material presented by the teacher. Based on the background of the problem, we propose to build an android based learning media that can help students learn independently, this application is called Letshoot. Letshoot were made as an instructional media of computer network troubleshooting that can help students learn independently without being hindered by place, time and teacher attendance. This research aims to develop and measure the feasibility level of Letshoot application. This app will help student to learn computer network troubleshooting. Using Borg and Gall's research and development model with the application developed in five stages: (1) data collection, (2) planning, (3) develop the preliminary form of product, (4) preliminary field testing, and (5) main product revision. The result of feasibility test of Letshoot application measured by using Likertscale from expert media get percentage 90,64% which belongs in very feasible category, from expert material equal to 82% which belongs very feasible category and from user equal to 82,11% which belongs to very feasible category to be used as a medium of learning. On these results can be concluded that the Letshoot application very feasible to use as a learning media of computer network troubleshooting in vocational high school